2023
DOI: 10.1002/jad.12180
|View full text |Cite
|
Sign up to set email alerts
|

The relation of classroom climate to adolescents' countering hate speech via social skills: A positive youth development perspective

Abstract: Introduction Hate speech is a current challenge for schools around the globe. At the same time, students worldwide stand up to hate speech by countering it. Guided by a positive youth development perspective, the present study investigated the direct and indirect associations between classroom climate (environmental assets), social skills (personal assets), and countering hate speech (as a proxy of thriving) among adolescents. Methods The sample included 3225 students in grades 7–9 (51.7% self‐identified as fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…The current study's identification of Defenders aligns with prior variable-centered research that has consistently highlighted the role of individual traits such as empathy, prosocial behavior, and assertiveness in predicting defending behavior (Wachs et al, 2024;Wachs et al, 2023b). The positive influence of a strong teacher-student relationship on the likelihood of a student becoming a Defender also resonates with past findings that supportive adult relationships are crucial to fostering student resilience and bystander intervention in bullying (Konishi et al, 2021;Mulvey et al, 2019;.…”
Section: Defenderssupporting
confidence: 77%
See 2 more Smart Citations
“…The current study's identification of Defenders aligns with prior variable-centered research that has consistently highlighted the role of individual traits such as empathy, prosocial behavior, and assertiveness in predicting defending behavior (Wachs et al, 2024;Wachs et al, 2023b). The positive influence of a strong teacher-student relationship on the likelihood of a student becoming a Defender also resonates with past findings that supportive adult relationships are crucial to fostering student resilience and bystander intervention in bullying (Konishi et al, 2021;Mulvey et al, 2019;.…”
Section: Defenderssupporting
confidence: 77%
“…Today, there is limited empirical evidence on the association between social skills and bystander behavior in the context of hate speech. One study revealed a positive connection to young people's willingness to counter hate speech (Wachs et al, 2023b). Other research found that empathy was positively related to countering hate speech, searching for help at school, and supporting the target but was negatively associated with reinforcing the perpetrator, revenge, helplessness, and ignoring (Wachs et al, 2024).…”
Section: Intrapersonal Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated a comparative investigation of training impacts with a health-preserving effect on students and mental states of self-actualization (Popovych et al, 2022b). It was explored by S. Wachs et al (2023) that the formation of social skills, which are in the plane of assertiveness, contributes to the strengthening of social and psychological climate of the class and serves as a prevention of hostile attitudes. It was found that with the increase of mindfulness and psychological well-being, anxiety demonstrated an inverse correlation and had a statistically significant advantage in the control group over the experimental group .…”
Section: Olesia Smolinskamentioning
confidence: 99%
“…В інших дослідженнях продемонстровано порівняльне дослідження тренувальних впливів зі здоров'язбережувальним ефектом студентів та психічними станами самоактуалізації . Досліджено S. Wachs et al (2023), що формування соціальних навичок, які лежать у площині асертивності, сприяє зміцненню соціально-психологічного клімату класу і є профілактикою ворожих настроїв. Досліджено, що зі збільшенням виміру уважності та психологічного благополуччя тривожність продемонструвала зворотну залежність і мала статистично достовірну перевагу в контрольній групі над експериментальною .…”
Section: Olesia Smolinskaunclassified